Perluasan Tanggungjawab Hukum Rumah Sakit Setelah Berlakunya Undang-Undang No. 17 Tahun 2023 tentang Kesehatan - Prilian Cahyani; Astutik; Yunita Dian Ashari; Nayla Sarachenita Arrsya (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
This research was motivated by changes in regulations regarding the responsibility of hospitals as corporations for losses resulting from negligence of health human resources in hospitals. UU Number 17 of 2023 concerning Health which was ratified on August 8 2023 was prepared using an omnibus law system. Several changes have occurred, one of which is the regulation of hospital legal responsibilities. As a result, legal issues arise regarding the expansion of the hospital's object of responsibility as a health services business entity for losses resulting from negligence. The aim of this research is to analyze the impact of changes in hospital responsibility arrangements on losses due to negligence of health human resources in hospitals. This research is normative juridical research using a statutory approach and a conceptual approach. The results of the research are changes in regulations regarding hospital legal accountability for hospital health workers as regulated in Law Number 44 of 2009 concerning Hospitals, which was later amended by the Health Law, means that the objects of responsibility of hospitals are expanded to include medical personnel, health personnel, and supporting personnel or supporting personnel called health human resources.